Le Conseil de l'Europe et les droits des minorités - Leuprecht, Peter (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
This survey deals with the problem of linguistic diversity in Europe. In what way does the Council of Europe react to what is commonly called there the « new minorities » composed of immigrants and refugees ? The Director for Human Rights at the Council of Europe first covers guarantees provided to members of minorities under the European Convention on Human Rights (article 14), then describes attempts made by the Council of Europe to protect minorities as such. As for the new minorities, the Council is taking action to favour intercultural education. Its policy aims a both preserving European languages in their diversity and encouraging multilingualism which is of such nature as to facilitate communication and understanding between different peoples